Cryptococcal Tongue Lesion in a Stem Cell Transplant Patient: First Reported Case. (17th July 2012) - Reinstadler, David R.; Dadwal, Sanjeet; Maghami, Ellie
Abstract : A compromised immune system places individuals at a significantly higher risk for many infectious processes. Immunosuppression also increases the risk of malignancy due to the body's decreased ability to perform its normal immunosurveilance and response. It is therefore imperative to have regular thorough evaluations of these patients, as slight abnormalities may be the early signs of infection or neoplasm. We present the first reported case of a tongue lesion in a stem cell transplant patient, highly concerning for malignancy, which was found to be a mucocutaneous presentation of disseminated Cryptococcus.